The Potential of Arable Weeds to Reverse Invertebrate Declines and Associated Ecosystem Services in Cereal Crops - Smith, Barbara M.; Aebischer, Nicholas J.; Ewald, Julie; Moreby, Steve; Potter, Caitlin; Holland, John M. (Frontiers in Sustainable Food Systems, 2020)
There is global concern that invertebrate populations are declining rapidly, particularly in agricultural habitats. Declines have been attributed to the intensification of farming systems, with many studies focussing on a lack of semi-natural habitat in the landscape and the use of insecticides. However, within-field arable weeds are also an important driver of invertebrate abundance and the ecosystem services to which they contribute. This study focuses on the role of arable weeds in supporting invertebrate populations and selected ecosystem services they deliver., using winter wheat as a case study. Weed-invertebrate relationships were investigated across seven studies of winter-sown wheat spanning 18 years. Both phytophagous and predatory invertebrates responded to weed cover but to different degrees. Phytophages showed a stronger positive relationship with weed cover than the predators, because they rely on the resources provided by the weeds whereas predatory species response is likely to be mediated by their prey. Farmland bird chick-food indices were positively related to both broadleaf and grass cover in cropped fields, indicating that increased weed cover can provide increased invertebrate food for birds in winter wheat. Despite this potential, there were insufficient invertebrate food resources for birds in the majority of wheat fields sampled. Weed diversity did not play a significant role in moderating the relationships between weeds and invertebrate abundance, however this may be a function of the low weed diversity in modern winter wheat fields. In this study the weed species most frequently shown to predict the invertebrate community were: Poa annua, Stellaria media, Fumaria officinalis, Sinapis arvensis, Senecio vulgaris, Persicaria lapathifolia, Sonchus spp., Matricaria discoidea, Persicaria maculosa, Agrostis spp., Lamium purpureum, Lamium album, Veronica spp., Atriplex spp., Myosotis spp. and Anagallis arvensis. We conclude that even in an intensively grown cereal, arable weeds can play an important role in maintaining and restoring invertebrate populations, that 10% weed cover is needed to fulfill the potential and that a successful outcome will be driven by the presence of weed species that support invertebrates that provide ecosystem services.